1990
DOI: 10.1021/bi00499a019
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous initiation due to slippage at the bacteriophage 82 late gene promoter in vitro

Abstract: RNAs synthesized in vitro by purified Escherichia coli RNA polymerase from a bacteriophage 82 promoter are heterogeneous at the 5' end. We show that this heterogeneity results from variable addition of extra adenine residues, allowed by slippage of the initial oligonucleotide pppAAA-OH against its DNA template sequence TTT. Slippage backward by one base allows another A to be added, giving pppAAAA-OH, and this cycle can continue more than 20 times before it is ended by incorporation of UMP encoded by the fourt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…Desired products from in vitro transcription of CQ1 (an A1G mutant of E. coli tRNA Gln ), CQ10 (a GC 4-69 AU mutant of CQ1), YF0 (yeast tRNA Phe ), CA0 (E. coli tRNA Ala ), and CA2 (a GC 4-69 CG mutant of CA0)+ method used for detecting these aberrant RNA products+ Transcripts prepared with 10% ATPaS and 90% ATP did not change the relative amount or position of the additional bands, indicating that the presence of the phosphorothioate containing NTP did not intrinsically produce the extra bands+ Transcriptions with either CTPaS or UTPaS instead of ATPaS also gave very similar patterns for the extra products, suggesting that the substituted ATPaS did not cause the extra products+ Finally, RNAs transcribed with only the four normal NTPs and [g-32 P] GTP were purified and subjected to partial digestion with RNase T1 to give specific cleavage after guanosines+ The minor bands observed by this method were identical in amount and distribution to those seen using phosphorothioate cleavage+ Two different mechanisms may explain the 59-terminal heterogeneity observed in the transcription products from T7 promoter sequences containing consecutive guanosine residues+ One possibility is that slippage occurs during the initiation processes such that, after the second nucleotide is added to form pppGpG, the dinucleotide can slip back by one residue in the enzyme active site prior to further elongation+ Such a mechanism has been proposed to explain 59-terminal heterogeneity produced by Escherichia coli RNA polymerase when initiating transcription with consecutive adenosines or uridines (Guo & Roberts, 1990;Xiong & Reznikoff, 1993)+ A related possibility is based on the observation that the large amount of abortive initiation products produced by T7 RNA polymerase can serve as primers for future initiation events (Moroney & Piccirilli, 1991)+ If one assumes that abortive products can reinitiate in an incorrect frame, 59 end heterogeneity would result+ More work is needed to clearly define the exact mechanism or mechanisms by which 59-terminal heterogeneity is produced by this polymerase+ Regardless of the mechanism, the presence of 59-terminal heterogeneity greatly complicates the isolation of RNA molecules with both length and sequence homogeneity because of the inevitable 39-terminal heterogeneity that results from premature termination and nontemplated additions of nucleotides by T7 RNA polymerase+ To illustrate this point, one of these tRNAs was subjected to a functional assay+ Using [a-32 P] CTP, CA0 was transcribed to a low specific activity, allowing the transcription products to be purified to single-nucleotide resolution on a polyacrylamide gel (Fig+ 3A)+ Each of the three major transcription products was assayed subsequently for its ability to be aminoacylated by E. coli alanyl-tRNA synthetase+ Because aminoacyl-tRNA synthetases require a 39-terminal CCA sequence in order to covalently attach an amino acid, the fraction of each band with a properly terminated 39 end can be estimated by measuring the amount of tritiated amino acid incorporated into the RNA+ As shown in Figure 3B, approximately 80% of the molecules in the proper sized Line integration of the radioactivity present near one expected adenosine for each RNA+ The major band is present at the left end of the trace, with positions ϩ1, ϩ2, and ϩ3 appearing to the right+ The percentage of radioactivity present in each peak is indicated+ transcript (76-nt long) are able to be aminoacylated+ The transcript one nucleotide shorter was only aminoacylatable to a very low level, whereas the transcript one nucleotide longer reached a level of approximately 55%+ These results correlate well with the RNA sequencing data+ Because none of the detectable 59 end heterogeneity se...…”
Section: Resultsmentioning
confidence: 99%
“…Desired products from in vitro transcription of CQ1 (an A1G mutant of E. coli tRNA Gln ), CQ10 (a GC 4-69 AU mutant of CQ1), YF0 (yeast tRNA Phe ), CA0 (E. coli tRNA Ala ), and CA2 (a GC 4-69 CG mutant of CA0)+ method used for detecting these aberrant RNA products+ Transcripts prepared with 10% ATPaS and 90% ATP did not change the relative amount or position of the additional bands, indicating that the presence of the phosphorothioate containing NTP did not intrinsically produce the extra bands+ Transcriptions with either CTPaS or UTPaS instead of ATPaS also gave very similar patterns for the extra products, suggesting that the substituted ATPaS did not cause the extra products+ Finally, RNAs transcribed with only the four normal NTPs and [g-32 P] GTP were purified and subjected to partial digestion with RNase T1 to give specific cleavage after guanosines+ The minor bands observed by this method were identical in amount and distribution to those seen using phosphorothioate cleavage+ Two different mechanisms may explain the 59-terminal heterogeneity observed in the transcription products from T7 promoter sequences containing consecutive guanosine residues+ One possibility is that slippage occurs during the initiation processes such that, after the second nucleotide is added to form pppGpG, the dinucleotide can slip back by one residue in the enzyme active site prior to further elongation+ Such a mechanism has been proposed to explain 59-terminal heterogeneity produced by Escherichia coli RNA polymerase when initiating transcription with consecutive adenosines or uridines (Guo & Roberts, 1990;Xiong & Reznikoff, 1993)+ A related possibility is based on the observation that the large amount of abortive initiation products produced by T7 RNA polymerase can serve as primers for future initiation events (Moroney & Piccirilli, 1991)+ If one assumes that abortive products can reinitiate in an incorrect frame, 59 end heterogeneity would result+ More work is needed to clearly define the exact mechanism or mechanisms by which 59-terminal heterogeneity is produced by this polymerase+ Regardless of the mechanism, the presence of 59-terminal heterogeneity greatly complicates the isolation of RNA molecules with both length and sequence homogeneity because of the inevitable 39-terminal heterogeneity that results from premature termination and nontemplated additions of nucleotides by T7 RNA polymerase+ To illustrate this point, one of these tRNAs was subjected to a functional assay+ Using [a-32 P] CTP, CA0 was transcribed to a low specific activity, allowing the transcription products to be purified to single-nucleotide resolution on a polyacrylamide gel (Fig+ 3A)+ Each of the three major transcription products was assayed subsequently for its ability to be aminoacylated by E. coli alanyl-tRNA synthetase+ Because aminoacyl-tRNA synthetases require a 39-terminal CCA sequence in order to covalently attach an amino acid, the fraction of each band with a properly terminated 39 end can be estimated by measuring the amount of tritiated amino acid incorporated into the RNA+ As shown in Figure 3B, approximately 80% of the molecules in the proper sized Line integration of the radioactivity present near one expected adenosine for each RNA+ The major band is present at the left end of the trace, with positions ϩ1, ϩ2, and ϩ3 appearing to the right+ The percentage of radioactivity present in each peak is indicated+ transcript (76-nt long) are able to be aminoacylated+ The transcript one nucleotide shorter was only aminoacylatable to a very low level, whereas the transcript one nucleotide longer reached a level of approximately 55%+ These results correlate well with the RNA sequencing data+ Because none of the detectable 59 end heterogeneity se...…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of all four NTPs, other promoters yield transcripts that are normal except that their 5' ends have more copies of the initiating nucleotide than are called for by the template sequence. The most clear-cut examples are transcripts that initiate with: oligo(U) pseudo-templated by As at the inSPL promoter of IS/ (Machida et al 1984); oligo(A) pseudo-templated by T4 at two promoters created by insertion of A : T-rich oligonucleotides in the spacer region of the tet promoter of pBR322 (Harley et al 1988(Harley et al , 1990; and oligo(A) pseudotemplated by T3 at the phage 82 PR' promoter (Guo and Roberts 1990). In these cases, the number of extra nucleotides at the 5' end is small, and the polymerase eventually switches from reiterative copying to truly ternplated transcription.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of all four nucleoside triphosphates (NTPs), the number of these extra "pseudo-templated" nucleotides varies from 1 to 8 or more, resulting in families of transcripts that have heterogeneous 5' ends (Machida et al 1984;Harley et al 1988Harley et al , 1990Guo and Roberts 1990). In all previously reported cases, the polymerase eventually switches to the conventionally ternplated mode if all four NTPs are present; at some of these promoters, RNAP produces homopolymers if the initiating NTP substrate alone is provided (see Discussion}.…”
mentioning
confidence: 99%
“…Such a mechanism has been proposed to explain the 5Ј end heterogeneity of RNA transcripts produced by the DNA-dependent RNA polymerases of E. coli and T7 bacteriophage (39)(40)(41). However, the templates in those studies contained homooligomeric nucleotides not found on the satC templates truncated by 3 or 4 bases.…”
Section: In Vitro Synthesis Of Satc By the Tcv Rdrp Using Templates Cmentioning
confidence: 99%